PERSEPSI PASIEN TENTANG MUTU PELAYANAN KEPERAWATAN DI RSUD AJIBARANG - Efendi, Muhamad Arif; Sumarni, Tri; Susanti, Indri Heri (Coping: Community of Publishing in Nursing, 2024)
Health services are considered quality if they are able to cause satisfaction for patients. There are five dimensions that can be assessed to measure patient satisfaction through the dimensions of quality of nursing services, namely the reliability dimension, the responsiveness dimension, the assurance dimension, the empathy dimension, the physical evidence dimension (tangible). This research was conducted to determine the description of patient perceptions regarding the quality of nursing services at Ajibarang Regional Hospital. This research was designed using quantitative descriptive analysis methods with a cross-sectional approach. This study involved 91 patients at Ajibarang Regional Hospital, sampled using accidental sampling. This research collects data using a questionnaire instrument that has been used by previous researchers. The research results showed that the majority of respondents were male, 48 respondents (52,7%), most had a high school education, 38 respondents (41,8%), and the majority were of adult age (26-45 years), 53 respondents (58,0%). The quality of service obtained by the majority of respondents found the quality of service at Ajibarang Regional Hospital in the good category as many as 60 respondents (65,9%), the majority of nurses were in the reliable category as many as 67 (73,6%), the majority of nurses had responsiveness in the responsive category as many as 67 (73,6%). Most patients received insurance in the guaranteed category as many as 66 (72,5%), most nurses had empathy with the empathy category as many as 61 (67,0%), most patients received physical evidence in the attractive category as many as 66 (72,5%).